Vision Sensors Recent Advances - Javier Gallegos-Funes, Francisco (IntechOpen, 2023)
Vision Sensors - Recent Advances reflects a selection of recent developments within the area of vision sensors and their algorithms. Among the image processing techniques involving the use of vision sensors are image measurement, image analysis, image transformation, image filtering, segmentation algorithms, supervised and unsupervised algorithms for classification, image recognition and parallel computing, and real-time algorithms. Recent literature reviews vision sensors with applications for localization of robot end effectors, panoramic vision sensors, wireless vision sensors, automated vision sensor inspection, multi-sensor imaging for medical data, and object recognition. This book brings together the work of a number of researchers and professionals who have made significant contributions to the field of vision sensors with image processing applications.